Should I rent my condo? : assessing risks of a property investment - Furfine, Craig (London : Kellogg School of Management, 2020)
In early 2018, Diana Mulhall was undertaking a career change that would eliminate the need for frequent business trips to Toronto. As a result, she wondered whether she should sell her condo in the heart of the Canadian city or keep it as a rental property to generate income for herself. The housing market in Toronto was booming, so Mulhall believed that the condo would fetch top dollar as a sale. She also thought it would be easy to attract tenants if she kept it as a rental. She had invested in rental property before but never outside of her hometown of Chicago, so Mulhall needed to identify the key risks associated with being a landlord in Toronto.
Originally Published InFurfine, C. (2020). Should I Rent My Condo? Assessing Risks of a Property Investment. 5-318-504. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Housing management -- United States; Housing management -- Ontario -- Toronto